PERAN EMOSI SEBAGAI VARIABEL YANG MEMEDIASI ANTARA STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN - Meiliana, Meiliana; Silintowe, Yunita Budi Rahayu (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2019)
This study aims to see the effect of store atmosphere on emotions and impact on purchasing decisions at Transmart Carrefour Semarang. The sample in this study were 272 respondents who had made a purchase decision on Transmart Carrefour Semarang. Data collection techniques using questionnaires with purposive sampling method. In testing the hypothesis, the data analysis technique uses Path Analysis. The results showed that the store atmosphere significantly influences emotions, and emotions significantly influence purchasing decisions, then the store atmosphere has a significant effect on purchasing decisions. Testing of intervening variables in this study shows that emotional variables can influence the indirect effect between store atmospheres on purchasing decisions.